2015
DOI: 10.1038/srep08124
|View full text |Cite
|
Sign up to set email alerts
|

Automated Analysis of Cell-Matrix Adhesions in 2D and 3D Environments

Abstract: Cell-matrix adhesions are of great interest because of their contribution to numerous biological processes, including cell migration, differentiation, proliferation, survival, tissue morphogenesis, wound healing, and tumorigenesis. Adhesions are dynamic structures that are classically defined on two-dimensional (2D) substrates, though the need to analyze adhesions in more physiologic three-dimensional (3D) environments is being increasingly recognized. However, progress has been greatly hampered by the lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…The relative sizes of populations of nascent versus maturing adhesions was shown to depend on ECM stiffness, and is important for overall cell migration rate. Broussard et al 54 recently automatically tracked several adhesion metrics, including adhesion size, adhesion lifetime, and assembly and disassembly rate constants for adhesions containing paxillin and vinculin in 3D collagen gels. They found a strong correlation between adhesion size and lifetime, a relationship recently established in 2D associated with vinculin-mediated tension 55 .…”
Section: Adhesion Kinetics In 3d Ecmsmentioning
confidence: 99%
“…The relative sizes of populations of nascent versus maturing adhesions was shown to depend on ECM stiffness, and is important for overall cell migration rate. Broussard et al 54 recently automatically tracked several adhesion metrics, including adhesion size, adhesion lifetime, and assembly and disassembly rate constants for adhesions containing paxillin and vinculin in 3D collagen gels. They found a strong correlation between adhesion size and lifetime, a relationship recently established in 2D associated with vinculin-mediated tension 55 .…”
Section: Adhesion Kinetics In 3d Ecmsmentioning
confidence: 99%
“…It has been demonstrated that 3D structures prompted cell attachment effectively than 2D substrates. [ 21 ] The well‐arranged macropores and the rough topography of BG@NbSiR scaffolds facilitate bone regeneration and integration (Figure 2j). [ 22 ] The related element distributions on a fractured BG@NbSiR scaffold indicated the uniform spreading of Si, O, and Ca, while Nb element only deposited on the surface of the scaffold (Figure 2k) due to the coating of Nb 2 C@SiR NSs, which further endowed the scaffolds with excellent photothermal performance and enhanced osteogenic capability.…”
Section: Resultsmentioning
confidence: 99%
“…Manual evaluation and analysis of FAs and SFs is a laborious, time-intensive process and is always at risk due to the observer's bias. Recently, this process has been aided by several automated analysis tools and algorithms that are optimized either for focal adhesion analysis (such as the Focal Adhesion Analysis Server [14] and other methods [15,16]), or stress fiber analysis (such as previous version of Filament Sensor [4], CytoSeg [17] and other tools [18,19]). However, a tool for speedy, unbiased quantification of SFs, FAs, and their mutual coupling is yet missing.…”
Section: Introductionmentioning
confidence: 99%